Fuzzy clustering as a tool for reducing subjectivity in the diagnosis of polymer insulators - da Costa Souza, João Pedro (2021)
The diagnosis of polymer insulators is a relevant topic of study and may present a high subjectivity. Thus, the present work aims to propose a methodology based on fuzzy clustering to reduce subjectivity in the diagnosis of polymer insulators. 60 polymer insulators with different degradation levels and nominal voltage of 138 kV were tested. The insulators were classified through visual inspection in three degradation levels: low, intermediate and critical. Then, the insulators were submitted to the following monitoring techniques: ultraviolet radiation detection, infrared thermography and ultrasound noise detection. Data from inspections were extracted and processed. For each monitoring method besides visual inspection, samples were grouped in three clusters. The clusters were associated to the degradation levels through detailed data analysis. A diagnosis was stablished considering the clusters from the three monitoring methods and results were compared to the diagnosis considering the visual inspection, and the most critical condition among them was considered. Five of the insulators presented a higher degradation level than the one stablished through visual inspection, so the methodology used would ensure the removal or supervision of the equipment. The proposed methodology reduces subjectivity in the diagnosis of polymer insulators while adding an unsupervised factor in the classification of its operational state.